Using Brownian bridges to assess potential interactions between bald eagles and electrical hazards within the upper Chesapeake Bay. Issue 3 (25th February 2015) - Watts, Bryan D.; Mojica, Elizabeth K.; Paxton, Barton J.
ABSTRACT: One of the most effective means of minimizing mortalities of large raptors from collisions with hazards is to locate hazards away from major activity centers. A reliable means of delineating bird activity centers on the landscape has been a significant impediment to progress in proactive infrastructure planning. We used Brownian bridge movement modeling to develop a population‐wide, utilization probability surface for bald eagles ( Haliaeetus leucocephalus ) within the upper Chesapeake Bay. We used locations ( n  = 320, 304) for individuals ( n  = 63) tracked with global positioning system (GPS) satellite transmitters between 2007 and 2011 in the analysis. We intersected the electrical network on the probability surface within Aberdeen Proving Ground, a 350‐km 2 military installation to identify overlap between power lines and eagle activity centers. We also overlaid locations of eagle mortalities attributed to the lines ( n  = 67) on the installation to assess the relationship between mortality rates and utilization probabilities. Areas of high bald eagle use were relatively rare on the landscape with only 0.1% and 5% of the area accounting for 10% and 30% of estimated utilization. Most electric lines were along roads and distributed away from eagle activity centers, with only 0.3% of lines located within areas with the highest estimated eagle use. Eagle mortalities were highly skewed to lines that overlapped with eagle activity centers. Eagle mortality rates (birds/100 km/yr) were 42 times higher along lines associated with the highest 10% of eagle use compared to lines associated with the lowest 10% use, suggesting that estimated utilization may be an effective proxy for mortality risk associated with electric line hazards. The majority (71.9%) of high‐use bald eagle areas delineated within the study area have no existing electric lines. Utilization probabilities may be a potential tool for site‐specific infrastructure planning. © 2015 The Wildlife Society.